Paweł Janiszewski, The Missing Link. Greek Pagan Historiography in the Second H alf of the Third Century and in the Fourth Century A D , The Journal of Juristic Papyrology Supplements VI, Warsaw 2006, David Brown Book Co., ss. XII + 531 - Anna Kotłowska (Vox Patrum, 2007)
recenzja